Processing Of Tofu Industrial Liquid Waste With Aeration And Adsorption Combined Methods In Reducing Levels Of Bod, Cod And Tss In Tofu Industry Pela Mampang, Mampang Prapatan Sub-District - South Jakarta 2018 - Desembra Lisa; Syarifuddin Syarifuddin; Rahayu Winarni (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2018)
Liquid waste from tofu production is generated from the washing, boiling, pressing and molding process. Liquid waste disposal from tofu production have temperature of 37-45°C, turbidity of 535-585 NTU, TSS, ammonia of 23.3-33.5 mg/L, BOD of 6000-8000 mg/l and COD of 7500-8400 mg/l. One of the techniques for the liquid waste processing from tofu production is aeration and adsorption. The purpose of this research is to know the combination of aeration and adsorption method in decreasing of BOD, COD and TSS in tofu wastewater at Pela Mampang tofu factory in Mampang subdistrict, South Jakarta in 2018. This research type is quasi experiment research, with research design of One Group Pre Test and Post Test Design. The sample of this research is tofu wastewater at Pela Mampang tofu factory in Mampang subdistrict, South Jakarta in 2018 with replication 5 times in each variation of contact time 20 minutes, 40 minutes, 60 minutes, 80 minutes and 100 minutes with observation parameters are BOD, COD and TSS. The results of the initial examination of BOD were 6244 mg/l, COD 33800 mg/l, and TSS 7100 mg/l. After being treated with a combined method of aeration and adsorption the BOD levels decreased to 4300.4 mg/l, COD 19283.6 mg/l, and TSS 5246.6 mg/l. There is a significant relationship between the time of treatment and reduction of BOD levels by 56.8%, while COD and TSS have no significant relationship.